2022
DOI: 10.1002/cpe.7228
|View full text |Cite
|
Sign up to set email alerts
|

Optimization techniques for task scheduling criteria in IaaS cloud computing atmosphere using nature inspired hybrid spotted hyena optimization algorithm

Abstract: Summary Cloud computing has garnered unprecedented growth in recent years in the field of Information Technology. It has emerged as a high‐performance computing option owing to its infrastructure that comprises of heterogeneous collection of autonomous computers and adaptable network architecture. The tasks that are scheduled in an optimized manner for their execution could be classified under NP‐hard problems. Though meta‐heuristic scheduling algorithms emerge as scheduling options, they need to be much more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is difficult to identify solutions and converge towards solutions for any type of workload generated through various users. Therefore, the authors in [ 26 ] formulated a scheduling mechanism to address violations of SLA, resource utilization and makespan. A hybrid multi-objective technique, i.e., QOGSHO, was used as a methodology in this approach.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to identify solutions and converge towards solutions for any type of workload generated through various users. Therefore, the authors in [ 26 ] formulated a scheduling mechanism to address violations of SLA, resource utilization and makespan. A hybrid multi-objective technique, i.e., QOGSHO, was used as a methodology in this approach.…”
Section: Related Workmentioning
confidence: 99%
“…The model was compared to ACO, GA, PSO, and WOA algorithms and SOATS was compared to CJS, MSDE, and FUGE approaches, and it was observed that SOATS optimizes cost and energy by 10% and 25%, respectively. In [ 25 , 26 , 27 , 28 , 29 , 30 ], the authors concentrated mainly on datacenter processing time, QoS parameters, and task processing time, and only one author in [ 28 ] discussed failure rate as all the existing task-scheduling algorithms discussed various parameters. But many of the authors did not tackle the relationship between fault tolerance and trust-based parameters.…”
Section: Related Workmentioning
confidence: 99%
“…RCOA shown huge impact while minimizing makespan. Multi objective scheduling technique developed by authors in 26 using QOGSHO by combining QOBL, SHO by designing an adaptive fitness function to evaluate SLA Violation, makespan, resource utilization. This experimentation conducted on a customized cloud environment.…”
Section: Existing Related Workmentioning
confidence: 99%
“…In our past web journal post, we expressed how to select between a private cloud and virtualization robotization. In this paper, we present the five questions you must ask after recently using IaaS [7][8][9]. IT infrastructure, like storage, servers, and networking resources, is managed by the cloud provider in the IaaS model and delivered to subscriber businesses via internet-accessible virtual machines.…”
Section: State Of the Artmentioning
confidence: 99%
“…Scheduling involves the allocation of virtual resources, the coordination of tasks, and the optimization of resource utilization. It plays a pivotal role in ensuring that cloud infrastructure operates at peak performance, meets service level agreements (SLAs), and makes the best use of available resources [8]. Infrastructure as a Service (IaaS) has revolutionized the way organizations manage and utilize computing resources.…”
Section: Introductionmentioning
confidence: 99%